Kewenangan Melakukan Pengawasan Pembagunan Kontruksi Speed Bump Pada Jalan - Tanda, Nunung Ramadan; Pattinasarany, Yohanes; Nirahua, Garciano (CAPITAN: Constitutional Law & Administrative Law Review, 2025)
The construction of speed bumps regulated in the Regulation of the Minister of Transportation Number 14 of 2021 concerning Amendments to the Regulation of the Minister of Transportation Number 82 of 2018 concerning Road User Control and Safety Devices, this supervisory authority is carried out to ensure that the construction of speed bumps is in accordance with the technical standards set out in the regulations. However, the construction of speed bumps is not in accordance with the regulations, making it difficult for motorized vehicle drivers to drive. For this reason, this paper examines 2 issues, namely which institution has the authority to supervise the construction of speed bumps on roads, how to supervise the construction of speed bumps on roads in Ambon City. Research method used is normative juridical, using a legislative approach, a conceptual approach, and a case approach. The law used is decision studies, journals, and internet media. The results of the study show that supervision of the construction and installation of speed bumps is the responsibility of several related institutions, depending on the location and type of road concerned. The local government, through the public works department or transportation department, has the authority to regulate and supervise the construction of speed bumps on local and regional roads. The installation of speed bumps must comply with the provisions stipulated in the Regulation of the Minister of Transportation Number 82 of 2018 concerning road user control and safety devices. Speed ​​bumps that do not meet the provisions can be subject to criminal sanctions. Therefore, the importance of supervision from the authorized institution to supervise speed bumps is the transportation department, which must obtain permission from the local transportation department.